Jumping Spider (Arachnida: Salticidae: Araneae) in Serang Residential Area, Banten: Inventory Study Using A Photographic Approach - Riski Andrian Jasmi; Herlina Putri Endah Sari; Muhammad Nazri Janra (Jurnal Biologi Tropis, 2022)
Ecosystem changes due to human activities can affect habitats for several organisms, such as spiders. Spiders have an important role as a predator for mosquitoes, flies, and ants. One of the spider families is Salticidae. Most species from Salticidae are cosmopolitan and often found in an area with dense human activity, such as residential areas. Study about spider species in residential areas is important to determine the effect of urbanization on spider diversity. This research aimed to study about spider species from Salticidae family found in the Serang Residential Area. The individual spider was caught directly by hand, then documented with macro photography techniques. Data analysis was carried out by describing the morphological characters. The results showed 5 species, namely Hasarius adansoni, Menemerus nigli, Menemerus fulvulus, Plexippus paykulli and Plexippus petersi. Documentation using good photography helps in making identification easier. This research is expected to be used as a reference for further research about a spider in a residential area.